HKROC: An integrated front-end ASIC to read out photomultiplier tubes for large neutrino experiments - Dulucq Frederic; Beauchêne Antoine; Bolognesi Sara; Bouyjou Florent; Carabadjac Denis; Conforti Di Lorenzo Selma; Firlej Miroslaw; Fiutowski Tomasz; Gastaldi Franck; Guilloux Fabrice; Idzik Marek; de La Taille Christophe; et al. (EPJ Web of Conferences)
The HKROC ASIC was originally designed to read out the photomultiplier tubes (PMTs) for the Hyper-Kamiokande (HK) experiment. HKROC is a very innovative ASIC capable to read out a large number of channels satisfying stringent requirements in terms of noise, speed and dynamic range. Each HKROC channel features a low-noise preamplifier and shapers, a 10-bit successive approximation Analog-to-Digital Converter (SAR-ADC) for the charge measurement (up to 2500 pC) and a Time-to-Digital Converter (TDC) for the Time-of-Arrival (ToA) measurement with 25 ps binning. HKROC is auto-triggered and includes all necessary ancillary services as bandgap circuit, PLL (Phase-locked loop) and threshold DACs (Digital to Analog Converters). This presentation will describe the ASIC architecture and the experimental results of the last prototype received in January 2022.